Examination of Fetal Indications in 548 Cases of Abortion Therapy Permissions Issued by Forensic Medicine Center of Razavi Khorasan, Iran, in 2015 - Nazila Badieian Mosavi; Seyed Aria Hejazi; Fatemeh Sadeghipour; Akram Fotovat; Marzieh Hoseini (Mashhad University of Medical Sciences, 2018)
Introduction: Congenital anomalies are originated during the egg fertilization or embryonic development and can cause life-lasting disability, illness, or mortality. The aim of this study was to determine the prevalence of anomalies based on fetal indications using the abortion cases permitted by forensic medicine organization and their related factors. Methods: This descriptive-analytic study was performed upon 550 mothers referring to the Mashhad Forensic Medicine Agency in 2015 due to fetal anomalies. The data collection tool was a checklist covering personal information, maternal pregnancy status, and fetal condition, which was designed using the opinions of professional experts. The data were analyzed in SPSS software (version 21) using Chi-square test. The confidence interval was considered at 95%. Results: The most common fetal anomalies observed in this study included central nervous system (CNS) anomalies (37.6%), followed by fetal renal (23.1%), genetic (14.7%), orthopedic (7.1%), gastrointestinal (6.1%), respiratory (6%), hematologic (5.9%), heart (4. 3%), and infectious (4%) disorders. Conclusion: the most common fetal disorder was related to the central nervous system. This disorder, which is unrecoverable, affects the body during the whole lifespan. Regarding this, the provision of people with education and awareness in this respect will have a significant effect on the prevention of these disorders in the whole society. Given the fact that the abortion permission can be issued before 20 weeks of gestation, it is essential to enhance mothers' awareness about paying attention to the risk factors and the importance of performing fetal health examinations.